Spatial Utilization Planning of Mangrove Conservation Area at Tinjul Village, Lingga Regency - Permana, Sendi; Sari, Yetti Anita; Harefa, Meilinda Suriani; Tuhono, Eling; Rahmadi, M Taufik; Lubis, Darwin Parlaungan; Damanik, M Ridha Safii; Ginting, M Rizky Pratama; Halim, Jennifer (Jurnal Penelitian Geografi (JPG), 2024)
The Indonesian Coastal Conservation Foundation (Yakopi) has successfully planted 82.24 hectares of mangroves in Tinjul Village, Lingga Regency. However, mangrove planting efforts need to be complemented with mangrove zoning mapping and the establishment of village regulations for mangrove protection. This research employs a qualitative approach using the Participatory Rural Appraisal (PRA) method, with data collection through Focus Group Discussions (FGD), participatory mapping, and documentation. The analysis method used is descriptive. The results indicate that (1) the first FGD led to an agreement on conducting mangrove zoning mapping and formulating village regulations, (2) a field survey via participatory mapping produced a mangrove zoning map, (3) the second FGD resulted in consensus on the mangrove zoning maps and village regulations regarding mangrove protection, and (4) the third FGD led to the ratification and handover of the mangrove zoning maps and Tinjul Village Regulation No. 002 of 2024 on mangrove protection to village government officials. The study concludes that community-based mangrove management can be sustainable, contributing to the balance of the existing ecosystem.Keywords: mangrove conservation; planning; spatial utilization